2021
DOI: 10.3390/ijms222212390
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Cryptococcus neoformans: From the Lab to the Clinic

Abstract: Fungal pathogens cause an array of diseases by targeting both immunocompromised and immunocompetent hosts. Fungi overcome our current arsenal of antifungals through the emergence and evolution of resistance. In particular, the human fungal pathogen, Cryptococcus neoformans is found ubiquitously within the environment and causes severe disease in immunocompromised individuals around the globe with limited treatment options available. To uncover fundamental knowledge about this fungal pathogen, as well as invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…As emphasized in this Review, the potential for exploration of diverse protease inhibitors against fungal pathogens exposes our limited knowledge of defined mechanisms of antifungal activity. This Review provides insight into selectivity and off-target effects to move the described in vitro studies from the lab bench and into the clinic [110]. Finally, while we focus on protease inhibitors with relevance against biomedical fungal pathogens, opportunities and applications presented in this Review extend, through crosstalk and cross-reactivity of protease inhibitors, to the plethora of fungal pathogens currently impacting the agricultural sector and threatening global food security.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…As emphasized in this Review, the potential for exploration of diverse protease inhibitors against fungal pathogens exposes our limited knowledge of defined mechanisms of antifungal activity. This Review provides insight into selectivity and off-target effects to move the described in vitro studies from the lab bench and into the clinic [110]. Finally, while we focus on protease inhibitors with relevance against biomedical fungal pathogens, opportunities and applications presented in this Review extend, through crosstalk and cross-reactivity of protease inhibitors, to the plethora of fungal pathogens currently impacting the agricultural sector and threatening global food security.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Moreover, we recently explored the source of such peptidase inhibitors from the natural environment, including plants, invertebrate, and microbes, presenting the strong evolutionary advantage of natural versus synthetic compounds (Gutierrez-Gongora and Geddes-McAlister 2021). Further, we recently presented integration of cryptococcal research at the bench with in vivo models of infection to move applications to the clinic for diagnosis, treatment, and understanding of cryptococcosis (Muselius et al 2021).…”
Section: Cryptococcal Peptidases As Druggable Targetsmentioning
confidence: 99%
“…An important technology for the discovery of novel proteases is mass spectrometry-based proteomics, which detects and quantifies proteins produced under a variety of experimental conditions and has application within both the lab and the clinic (Aebersold and Mann 2016;Zhu et al 2021). For many fungal pathogens, proteomics is a promising tool to further our understanding of pathogenesis, define signaling networks, explore interactions with the host, develop biomarkers for diagnostics, as well as assess treatment efficacy Ball et al 2019;Ball et al 2020;Muselius et al 2021;Retanal et al 2021). Additionally, peptidases produced by the fungus can be measured within the intracellular (cellular proteome) and extracellular (secretome) environments for identification.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent developments in mass spectrometry (MS)-based proteomics provide a promising approach for identifying the related molecular mechanisms. Proteomics is a sensitive and robust approach for identifying proteins and pathways associated with fungal pathogenesis, drug resistance, modulation of host immune response, and the discovery of drug targets (17)(18)(19). For example, comparative proteomics has revealed that energy metabolism and cell stress were related to acquired fluconazole resistance in C. albicans (19).…”
Section: Introductionmentioning
confidence: 99%